Bacterial diversity in Bercaea Cruentata gut described using high-throughput sequencing. (December 2015) - Long, L.L.; Guo, J.J.; Li, P.; Guo, Y.D.
Abstract: The investigation of postmortem interval (PMI) is the main and important course for forensic examination. Forensic entomology is a useful tool to estimate scientifically the time elapsed since death. Since bacteria play a critical role in attracting insects to cadavers, it is essential for forensic scientists to understand the interactivation between bacteria and insects. This study aimed to investigate gut bacteria diversity of Bercaea cruentata . The gut microflora was collected from adult and third instars larvae of B. cruentata. DNA technologies was used (high-throughput sequencing of 16S rRNA amplification on Illumina MiSeq platform) to catalog the bacterial community. Operational taxonomic units (OTUs) were of higher abundance in adult group, and Firmicutes and Proteobacteria were both predominated in larvae and adult groups. Our study provided data on gut bacteria diversity of B. cruentata for the first time. Bacterial community in adult B. cruentata gut were observed different taxon richness and relative abundance patterns compared with the larvae gut, but both adult and larvae have preferences for specific bacteria species. Further studies are required to verify the signaling mechanism for bacterial attraction of sarcosaphagous insects.